Field-scale biopiles for remediation of sulfolane-contaminated soil. Issue 3 (21st January 2021) - Yu, Linlong; Mulder, D'Arcy Winifred; Giurici, Art; Keir, Ian; Hollman, Jordan; Achari, Gopal
Abstract : Sulfolane is an organosulfur solvent, which has been widely used to remove acid components from sour natural gas. In recent years, it has been detected in soil and groundwater near gas-processing plants in North America, becoming a potential threat to ecosystems and human health. Previous bench-scale studies have shown that aerobic degradation is a promising method for treating sulfolane in contaminated soil. In this study, field-scale aerobic biopile technologies were evaluated to treat sulfolane-contaminated soil in western Alberta, Canada. Six field-scale (25–300 m 3 ) soil biopiles with different nutrient and aeration conditions were constructed on the sulfolane-contaminated site. The sulfolane concentration, carbon dioxide (CO2 )/oxygen (O2 ) level and moisture content in the soil piles were monitored throughout the remediation period. The results indicated that sulfolane can be degraded slowly in the soil biopiles without nutrient addition and aeration. The soil biopiles with nutrient addition and aeration yielded the best performance in degrading sulfolane with a rate of 42 (mg/kg)/day. It is concluded that soil biopiles is an effective technology to remediate sulfolane-contaminated soil under field conditions.